DEVELOPING STUDENTS’ WRITING SKILL THROUGH JIGSAW, MIND-MAPPING, AND ROUNDTABLE TECHNIQUES - Dwi Iswahyuni; Sri Kiswati (UNMUHBABEL Press, 2019)
Writing skill seems to be a difficult skill for many students. Whereas, they are demanded to be able to write at text level. This study investigates how students’ writing skill can be developed through the combination of jigsaw, mind-mapping, and roundtable techniques. The aim of the study was to find out in what ways the combination of jigsaw, mind-mapping, and roundtable techniques can develop students’ writing skill. Moreover, this study belonged to a pre-experimental study and the instruments employed in this study were tests and field notes. The results of the study showed that almost all of the students made some improvements after the treatments. All aspects which comprised grammar; mechanics; style and quality of expression; organization; and content aspects were improved. In addition, the highest improvement belonged to grammar aspect (30.73%). Furthermore, based on the field notes, the students gave positive responses towards the treatments and the treatments were worthwhile for the development of the students’ writing skill. Based on the results of the study, it can be concluded that the combination of jigsaw, mind-mapping, and roundtable techniques can develop students’ writing skill in many ways including grammar, mechanics, vocabulary, organization, and content aspects.